Porphyrin-terminated nanoscale fluorescent polyrotaxane as a biodegradable drug carrier for anticancer research. (9th April 2020) - Zhang, Yi; Jia, Shuxin; Yuan, Jintao; Zhu, Peide; Gan, Ying; Fan, Guangfang; Yu, Shuling; Shi, Jiahua
Abstract: Drug delivery carriers hold tremendous promise for improving cancer treatment, and polyrotaxane (PR) has shown excellent drug-carrying properties. However, there have been some reports that, when used as a drug carrier, water-soluble PR is not easily labeled with organic fluorescent dyes. Herein, we synthesized a drug-loaded fluorescent porphyrin-terminated PR (PR-COOH) which can be used as a tracer material in drug and gene delivery. The structure, morphology and zeta potential of PR-COOH were characterized by nuclear magnetic resonance, high-resolution transmission electron microscopy and zeta potentiometry. In this research, cisplatin (CDDP) is used as a model drug. The zeta potential, drug encapsulation efficiency and drug release of CDDP-loaded PR (PR-COOH-Pt) were studied. Confocal laser scanning microscopy showed that PR-COOH could be internalized by HeLa and CT26 cells. The antitumor efficacy of PR-COOH-Pt was investigated in vitro by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay and in vivo by a xenograft tumor model. The results showed that PR-COOH-Pt could significantly inhibit tumor growth; thus PR-COOH-Pt has a promising role in cancer therapy.